Analisis Standarisasi Material dan Optimasi Proses Produksi pada Pembuatan Keripik Pisang - Muti, Asri Amalia; Syarofah, Feti (Politeknik ATI Padang, 2025)
This study aims to analyze the need for material standardization and to formulate process optimization strategies in the production of banana chips at UD. FAVORIET. Quality instability was identified during the period of August–September 2021, indicated by a total defect weight of 28.875 kg from a total production volume of 323 kg. The defects consisted of burnt chips (11.375 kg) and non-crispy or soft chips (17.5 kg). The analysis was conducted by evaluating the standards of raw materials (banana type, ripeness level, slicing thickness), process parameters (oil temperature, frying time, stirring method), and operator-related factors. The results show that high defect levels were caused by inconsistent material quality, variations in slice thickness, unstable frying temperature, and insufficient operator control. Optimization recommendations include standardizing slice thickness at ±2 mm, selecting bananas with 70–80% ripeness, maintaining frying temperature at 150–160°C, setting frying duration between 10–12 minutes, and providing regular operator training. The implementation of these standards is expected to improve production stability and significantly reduce defect rates.